An Analysis of Grammatical Errors Found in Regulation of The Minister of Religious Affairs of the Republic Indonesia Number 2 of 2022 at the Halal Product Assurance Organizing Agency (BPJPH) Indonesia - Ramadhan, Annelia; Rahayu, Rahayu (Edu-Ling: Journal of English Education and Linguistics, 2023)
In Indonesia, the Ministry of Religious Affairs Regulation (PMA) number 2 of 2022 discusses the procedures for halal certification for imported products into Indonesia. The aim of this research is to analyze the grammatical errors and identify the factors that cause the grammatical errors found in the translation of the Minister of Religious Affairs Regulation Number 2 of 2022, conducted by MSIB  Batch 2  interns’ students in the English section at the Halal Product Assurance Organizing Agency (BPJPH). The data source for the research is taken from the Translation Document of the Minister of Religion Regulation Number 2 of 2022. This research will use observation and recording methods to analyze descriptively the grammatical errors and identify the factors causing errors in translation documents. The results of the analysis showed that the percentage for each type of error was 36.875% (Interlanguages errors), 62.5% (Intralingual errors), and 0.625% (Developmental errors). Then the causing factor of the error is influenced by the translator's first language, a lack of understanding of the target language's writing structure, failure to apply the correct structure, and a lack of understanding of the difference  in  writing  structure  between  the  source  and  target  languages.  This  research  is expected to contribute to developing the field of translation linguistics and improving professionalism in translating official documents. Keywords: Ministry of Religious Affairs Regulation, Translation, Grammatical error, Halal Product Assurance Organizing Agency (BPJPH)